Synergistic dual-modified liposome improves targeting and therapeutic efficacy of bone metastasis from breast cancer - Xianzhu Ke; Wen Lin; Xiaokang Li; Hailiang Wang; Xin Xiao; Zheng Guo (Taylor & Francis Group, 2017)
Breast cancer frequently metastasizes to bone, where it leads to poor clinical prognosis. Due to the peculiarity of the bone microstructure, the uptake of drugs often happens at non-targeted sites, which produces a similar cytotoxicity in both cancerous and healthy cells. In this study, a rational strategy was implemented to take advantage of a combination of both an octapeptide with eight repeating sequences of aspartate (Asp8) and folate to create a more selective and efficient drug delivery system to target cancer cells in bone tissue. Asp8 and folate were conjugated to the distal ends of DSPE-PEG2000-maleimide and DSPE-PEG2000-amine to create DSPE-PEG2000-Asp8 and DSPE-PEG2000-Folate, respectively, which were incorporated onto the surface of a doxorubicin (DOX)-loaded liposomes (A/F-LS). Asp8, similar to the hydroxyapatite-binding domains of osteopontin and osteocalcin, has been used as bone-targeting moieties for exclusive delivery of drugs to bone. The folate moiety binds selectively to folate receptor-positive tumors. The dual-targeting effects were evaluated by both in vitro and in vivo experiments. By taking advantages of dual-targeting drug delivery, the dual-modified liposomal drug system could relieve pain and improve survival. Inspired by its enhanced therapeutic efficacy and low toxicity, DOX-loaded A/F-LS could serve as an effective drug system for targeted therapy of bone metastases.